Quantitative Easing in the Euro Area - An Event Study Approach - Florian Urbschat; Sebasitan Watzka (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We examine the effects of the QE programme started by the ECB in 2015. Studying the short-term reaction of bond markets, we try to quantify different asset price channels such as the portfolio rebalance channel by running event regressions for several Euro Area countries. Our analysis suggests that the ECB's policy had strong and desired effects on bond markets at the very beginning, but less so subsequently. Possible explanations are the increasingly burdensome institutional set-up of the APP.
Keywords: E43; E44; E52; E58; G14; 330